Exploring the link between Training Transfer Climate and Work Engagement among Clinical Nurse Specialists in China: the mediating role of Craftsmanship Spirit - Renxiu Wang; Rongjian Ji; Junyan Zhao; Lei Qin; Shuangshuang Zhang; Xinru Liu; Hongxia Song (BMC Nursing)
Abstract Background Clinical nursing specialists are essential in emergency care, chronic disease management, and telehealth.Their work engagement is increasingly tied to training quality, particularly through the professional values embodied in the Craftsmanship Spirit. This study aims to explore the mediating role of Craftsmanship Spirit in the relationship between Training Transfer Climate and Work Engagement among Clinical Nurse Specialists in China. Methods A cross-sectional assessment of 416 clinical nursing specialists from 19 provinces and cities in China was conducted using validated scales: General socio-demographic information, specialist nurses’ work commitment, craftsmanship, and training migration climate. All statistical analyses were conducted using R software (version 4.3.2). Confirmatory Factor Analysis (CFA), Structural Equation Modeling (SEM), Visualizations of the path model and correlation heatmaps were used to analyze the relationship between clinical nurse training migration climate, work engagement, and craftsmanship. Results All correlations were statistically significant (p < 0.001). The goodness-of-fit indices for the structural model are presented (χ²/df ratio of 1.066, CFI = 0.995, TLI = 0.995). The indirect effect of TTC on WE via CS was statistically significant (β = 0.331, SE = 0.042, 95% CI [0.256, 0.418]). TTC’s direct effect on WE was insignificant (β = 0.026, p = 0.607), suggesting that CS fully mediated this relationship. The total impact of TTC on WE was significant (β = 0.357, SE = 0.048, 95% CI [0.256, 0.455]), with the proportion mediated reaching 92.7%, highlighting the central role of Craftsmanship Spirit in linking training climate to engagement outcomes. These results emphasize that a favorable training transfer climate enhances nurse engagement primarily by fostering a strong craftsmanship orientation. Conclusion Craftsmanship is essential for clinical nursing specialists to fully mobilize the level of work engagement to improve under the threat of insufficient organizational training and relocation atmosphere. Nursing managers should pay attention to the influence of these factors mentioned above to stimulate the formation of artisanship in clinical nursing specialists, which is conducive to nurses’ cultivation of enduring enthusiasm for work engagement and the formation of high-quality nursing safety. Clinical trial number YXLL-KY-2024 (156).